Sex in Australia: Sexual and emotional satisfaction in regular relationships and preferred frequency of sex among a representative sample of adults - Juliet Richters; Andrew E. Grulich; Richard O. deVisser; Anthony M.A. Smith; Chris E. Rissel (Elsevier, 2003)
Abstract Objectives : To document sexual and emotional satisfaction with their relationships and desired and actual frequency of sex among a representative sample of Australian adults. Method Between mid‐2001 and mid‐2002, computer‐assisted telephone interviews were completed by 10,173 men and 9,134 women aged 16-59 years from all States and Territories selected by modified random‐digit dialling of households (response rate 73.1%). Respondents in a regular relationship were asked how physically pleasurable they found sex with the partner to be and how emotionally satisfying the relationship was. All respondents were asked how often they would ideally like to have sex and how often they had sex in the past four weeks. Results : Most people in heterosexual relationships found sex very or extremely pleasurable (90.3% men, 79.1% women) and the relationship emotionally satisfying (87.5% men, 79.2% women); men were more satisfied with both. Physical pleasure in sex was correlated with emotional satisfaction. One person in four had had no sex in the past four weeks; most people had had sex less than twice a week. Most people wanted ideally to have sex more often than they did. However, 24.3% of men but only 8.3% of women said they ideally wanted sex daily or more often. Conclusion Men on average express higher levels of relationship satisfaction and of sexual interest, but the overlap between men and women is large.